Epidemiological and Clinical Characteristics of Cat Scratch Disease in Adults in Lima, Peru. Case series. and literature review - Maguiña-Vargas, Ciro (2025)
Objectives: To determine the epidemiological and clinical characteristics of cat scratch disease in adults in Lima, Peru. Methods: Descriptive, retrospective study carried out at the Hospital Nacional Cayetano Heredia in Lima and a Private Center in Lima, in the period between 2016 and 2025, in patients over 18 years of age. Results: Of eleven patients with cat scratch disease (CSD), ten presented the typical picture, the only patient affected by neuroretinitis did not present any lymph node symptoms, she did present fever of obscure origin and decreased visual acuity, 10 patients had positive IFA serology to Bartonella henselae (IgG and IgM), only one clinical and epidemiological CSD, six received azithromycin, one doxycycline, one combination of azithromycin + clindamycin, one azithromycin + doxycycline, one doxycycline + rifampicin; One case received azithromycin + gentamicin. The outcome was favorable in all. Conclusions: All patients had contact with cats, the vast majority had right epitrochlear lymph node involvement, only one case presented with fever of unknown origin and neuroretinitis, and 90.9% had serology + IIF for Bartonella henselae.